The Role of Artificial Intelligence in Shaping Privacy Laws: A Comparative Analysis of Global Regulatory Frameworks - Any Farida (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The rapid advancement of Artificial Intelligence has significantly transformed the processing and utilization of personal data, creating increasingly complex privacy challenges that extend beyond the scope of conventional data protection frameworks. Existing privacy laws in many jurisdictions have struggled to keep pace with the evolving capabilities of AI technologies, particularly regarding automated decision-making, algorithmic processing, cross-border data transfers, and large-scale data analytics. These developments have prompted governments and international organizations to reform legal frameworks in order to establish effective AI governance while maintaining the protection of fundamental rights and supporting technological innovation. This study aims to comparatively analyze privacy law frameworks governing Artificial Intelligence across major jurisdictions and to examine the regulatory gaps and future directions for AI-oriented privacy law reform. This research employs normative legal research using statutory, comparative, and conceptual approaches by analyzing international legal instruments, national legislation, and relevant scholarly literature concerning privacy protection and Artificial Intelligence governance. The findings demonstrate that the European Union, the United States, China, and Indonesia have adopted distinct regulatory approaches reflecting different legal traditions, governance priorities, and policy objectives, resulting in varying levels of protection, accountability, enforcement, and AI oversight. The study further identifies fragmented regulations, jurisdictional conflicts, cross-border data transfer issues, algorithmic accountability, transparency concerns, and enforcement limitations as the principal legal challenges that continue to hinder the effectiveness of global AI governance. Accordingly, future privacy law reform should prioritize adaptive and risk-based regulation, strengthen international regulatory harmonization, integrate privacy by design and human oversight into AI governance, and promote global cooperation to establish a balanced legal framework capable of safeguarding privacy while supporting responsible Artificial Intelligence innovation.